Risk factors of neonatal mortality in sanglah hospital denpasar - Lufyan, Reddy; Kardana, Made; Subanada, Ida Bagus (Medicina; Vol 47 No 3 (2016): September 2016, 2016)
The neonatal mortality continues to be one of the global burden for both developed and developing countries. Information on neonatal mortality at international level is in great demand because it emerges as an increasingly prominent component of overall under-five mortality. Since causes of neonatal death vary by country and with the availability and quality of health care, understanding neonatal mortality in relation to these factors is crucial. This study aimed to acknowledge the characteristics and identify the related risk factors of neonatal mortality in Sanglah Hospital Denpasar. This study was a case control study performed in Sanglah Hospital Denpasar. Data was obtained from medical record and registry, analyzed as bivariate using chi-square test and multivariate by using logistic regression analysis model. This study involved 96 subjects for each case and control group. Bivariate analysis showed that asphyxia, low birthweight, major congenital anomaly, prematurity, respiratory distress syndrome, and sepsis were risk factors of neonatal mortality. Multivariate analysis showed that major congenital anomaly (OR 15.67; 95%CI 3.43 to 71.57), prematurity (OR 4.99; 95%CI 1.23 to 20.17), and respiratory distress syndrome (OR 34.90; 95%CI 12.79 to 95.26) were the most significant risk factors of neonatal mortality. In conclusion, neonatal mortality is still an important issue to be concerned seriously. Respiratory distress syndrome, major congenital anomaly, and prematurity were the most significant risk factors associated to neonatal mortality. Better understanding of the risk factors would increase the clinical awareness, develop, and improve better service for neonatal care to reduce neonatal mortality rate.   Keywords: risk factor, neonatal, mortality